Zeolite as carrier of inorganic and organic corrosion inhibitors for aluminum alloy AA2024-T3 - Ferrer, Emmanuel L. (2013)
The ability of NaY zeolite as a microporous carrier of both inorganic and organic corrosion inhibitors for aluminum alloy AA2024-T3 is investigated in this work. The corrosion inhibitors were selected based on their molecular size and anti-corrosive properties for aluminum alloys. Corrosion tests using potentiodynamic polarization method (PPT) reveal that 1mM concentrations of inhibitors cerium nitrate hexahydrate (Ce), aminotrimethylene phosphonic acid (ATMP) and sodium diethyldithiocarbamate trihydrate (DEDTC) each in 0.05M NaCl solution exhibit good corrosion protection for AA2024-T3 at neutral, slightly acidic and slightly basic conditions, respectively. These corrosion inhibitors were successfully incorporated individually and in combination to the zeolite carrier via ion-exchange and adsorption procedure to develop different anti-corrosive pigments. The corrosion protection of the created pigments on AA2024-T3 was also evaluated in 0.05M NaCl solution using the PPT method. Results reveal that only NaY-Ce-DEDTC (NaY doped with cerium followed by diethyldithiocarbamate) provides both fast-release action and sustained corrosion protection for the alloy substrate in aqueous NaCl solution. Equilibrium isotherm experiments suggest that Ce ion-exchange with NaY obeys the Langmuir isotherm model (R² = 0.962) while DEDTC adsorption on NaY-Ce follows the Temkin model (R² = 0.769). Kinetic experiments on Ce ion-exchange with NaY and DEDTC adsorption on NaY-Ce reveal that both processes follow the Pseudo-second order rate equation model at R2 value of 0.999 and 0.925, respectively. Sol-gel coatings with 10% by weight of the selected pigments along with NaY zeolite as reference were prepared and applied to AA2024-T3 panels. An artificial scratch defect was made on the coated panels to expose the substrate in 0.05M NaCl solution for several days. Electrochemical impedance measurements on the low frequency region reveal that self-healing was observed after 2-days of immersion in the corrosive media for both NaY-Ce and NaY-Ce-DEDTC. Moreover, phase angle measurements reveal that shift to lower frequencies was observed for the coatings doped with the pigments suggesting decrease in corrosion rate. An increase of phase angle for NaY-Ce-DEDTC was also observed at 19 days of immersion suggesting better and more stable protection for AA2024-T3 at longer immersion time in 0.05M NaCl solution.
Dissertation (Ph.D. Chemical Engineering)--University of the Philippines, Diliman
Keywords: Zeolites; Corrosion resistant materials; Aluminum alloys